Peran Orang Tua dalam Pembentukan Kepribadian Islami Anak - Putri Maja Mulia Kulzum (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
Being a parent is not easy, it needs further learning which unfortunately is never taught in schools. For many things, parents are responsible for the growth and development of their children later. Teaching children to be good and have morals that can be said to be difficult is all because the logic in children is not fully developed, requires a special way to handle it, namely through habituation from an early age to build a positive child's personality. A child as a good imitator will do whatever they see, so parents in this case need to be good role models for children. If it is like the wise saying that an apple never falls far from the tree, it means that children are a reflection of their parents. If parents want to have children with good character, parents must have good character as well. So that parents have a major role in fostering children at an early age. Every child is like a clean white paper, they will follow every direction their parents give them. Not only parents, schools and the surrounding environment also play a major role in the formation of children's character. But again, if parents have put good character values, they will not absorb and be influenced by other things from their environment that can damage the child's character, which means that the role of fathers and mothers in the family is important in the formation of this child's character. In addition, the responsibility of parents for the formation of children's character needs to be their main concern.